2022
DOI: 10.15376/biores.18.1.100-110
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the physical properties and decay resistance of bamboo materials via modification with boric acid and borax

Abstract: As a renewable biomaterial, bamboo has been widely used in construction and indoor decoration. While the application of bamboo is limited by its low decay resistance and flame retardancy, the combination of modification with boric acid and borax has been found to be effective for improving bamboo flame retardant. In this study, the decay resistance, mechanical properties, and physical properties of bamboo, both before and after treated being with boric acid and borax (in a 1 to 2 ratio), were analyzed to bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Material thermal conductivity should not exceed 0.08 W/mK for insulation applications [6]. Some other relevant parameters include resistance to water vapor diffusion, water absorption, moisture content [7], low thermal transmittance (U in W/ m²K) [5], and adequate resistance to bending, tension [8], compression, fungal growth, and flame retardancy [9][10][11]; this last is referred to material's behavior 2 under fire conditions or fire-proofing property, while the mold growth test verify the effectiveness of adding borax or other element, in the decrease of fungal growth [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Material thermal conductivity should not exceed 0.08 W/mK for insulation applications [6]. Some other relevant parameters include resistance to water vapor diffusion, water absorption, moisture content [7], low thermal transmittance (U in W/ m²K) [5], and adequate resistance to bending, tension [8], compression, fungal growth, and flame retardancy [9][10][11]; this last is referred to material's behavior 2 under fire conditions or fire-proofing property, while the mold growth test verify the effectiveness of adding borax or other element, in the decrease of fungal growth [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…One modification that has the potential to improve the quality of bamboo as a raw material for laminated boards is boric acid. Liu [17] reported that boric acid was successfully used for wood modification. The research showed that wood's physical, mechanical and durability properties increased with this modification.…”
Section: Introductionmentioning
confidence: 99%